1955
DOI: 10.1113/jphysiol.1955.sp005267
|View full text |Cite
|
Sign up to set email alerts
|

Preferential transference of amino‐acids from amino‐acid mixtures by sacs of everted small intestine of the golden hamster (Mesocricetus auratus)

Abstract: The ability of the small intestine to transfer amino-acids against a concentration gradient has been demonstrated by a number of investigators in the past few years (Wiseman, 1953;Agar, Hird & Sidhu, 1953;Smyth & Whaler, 1953;Wilson & Wiseman, 1954). The results of those investigations have shown that an active mechanism exists for the absorption of certain L-amino-acids but not for their D-forms. The L-amino-acids which those workers showed to be actively transferred by the small intestine of the rat are alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2
2

Year Published

1955
1955
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 8 publications
4
46
2
2
Order By: Relevance
“…The ability of the RD3 sarcoma cells in suspension to take up amino-acids against a concentration gradient is well marked and the mechanism is active for the diamino-acids as well as for the mono-aminoacids. This is in contrast to the findings with hamster small intestine (Wiseman, 1955) which can transfer against a gradient only the mono-amino-acids but not the diamino-acids. The concentration ratios developed by the sarcoma cells and the hamster small intestine (Wiseman, 1955) are of the same order, although the intestine concentrates proline better than histidine, while the sarcoma cells concentrate histidine better than proline.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The ability of the RD3 sarcoma cells in suspension to take up amino-acids against a concentration gradient is well marked and the mechanism is active for the diamino-acids as well as for the mono-aminoacids. This is in contrast to the findings with hamster small intestine (Wiseman, 1955) which can transfer against a gradient only the mono-amino-acids but not the diamino-acids. The concentration ratios developed by the sarcoma cells and the hamster small intestine (Wiseman, 1955) are of the same order, although the intestine concentrates proline better than histidine, while the sarcoma cells concentrate histidine better than proline.…”
Section: Discussioncontrasting
confidence: 55%
“…This is in contrast to the findings with hamster small intestine (Wiseman, 1955) which can transfer against a gradient only the mono-amino-acids but not the diamino-acids. The concentration ratios developed by the sarcoma cells and the hamster small intestine (Wiseman, 1955) are of the same order, although the intestine concentrates proline better than histidine, while the sarcoma cells concentrate histidine better than proline. With both these tissues it was found that poorly concentrated amino-acids act as better inhibitors than amino-acids which are well concentrated.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Later results (VISEMAN, 1953;AGAR et al, 1953;MATTHEWS and SMYTH, 1954) showed that transport of L-amino acids involves an active process and it was assumed that this did not apply to D-amino acids. On the other hand, JERVIS and SMYTH (1959) showed that competition between some Dhistidine and L-Met was possible using in vivo as well as in vitro techniques (WISEMAN, 1955). In the later work, JERVIS and SMYTH (1960) suggested that the transfer mechanism for L-Met has not been absolutely stereochemically specific and that D-Met is able to utilize this mechanism in vitro.…”
Section: Experiments Designmentioning
confidence: 99%